Product management - LeMay, Matt; Bolton, Mitch (O'Reilly Media, 2019)
How does a product manager successfully connect and align their team? By leveraging the CORE skills of product management: communication, organization, research, and execution. This infographic describes the core skills needed for a product manager to succeed at your organization.